Short-term application of biochar improves post-heading crop growth but reduces pre-heading biomass translocation in rice - Xiaohong Yin (Plant Production Science, 2020)
Although biochar has potential benefits in environmental and agronomic aspects, short-term application of biochar to rice does not increase grain yield. The objective of this study was to identify the crop growth characteristics responsible for why applying biochar over the short-term does not increase grain yield in rice, thus providing information for how to increase grain yield in rice following short-term application of biochar. Field experiments were conducted to investigate the effects of biochar application (20 t ha–1) on yield attributes and crop growth characteristics in rice grown under two N rates in two years. Results showed that biochar application had no significant effects on grain yield or yield components. Biochar application increased radiation use efficiency and biomass production during post-heading and total biomass production by 7–16%. Pre-heading biomass translocation and harvest index were decreased by 4–11% with biochar application. These results indicate that the lack of increased yield in rice following short-term application of biochar is attributable to compensation between increased biomass production resulting from improved post-heading crop growth and decreased harvest index resulting from reduced pre-heading biomass translocation. The finding of this study suggests that establishing a compatible relationship between post-heading crop growth and pre-heading biomass translocation is critical for increasing grain yield in rice following application of biochar over the short-term.